Tus, an E. coli protein, contains mammalian nuclear targeting and exporting signals. - Stanislaw J Kaczmarczyk; Kalavathy Sitaraman; Thomas Hill; James L Hartley; Deb K Chatterjee (PLoS ONE)
Shuttling of proteins between nucleus and cytoplasm in mammalian cells is facilitated by the presence of nuclear localization signals (NLS) and nuclear export signals (NES), respectively. However, we have found that Tus, an E. coli replication fork arresting protein, contains separate sequences that function efficiently as NLS and NES in mammalian cell lines, as judged by cellular location of GFP-fusion proteins. The NLS was localized to a short stretch of 9 amino acids in the carboxy-terminus of Tus protein. Alterations of any of these basic amino acids almost completely abolished the nuclear targeting. The NES comprises a cluster of leucine/hydrophobic residues located within 21 amino acids at the amino terminus of Tus. Finally, we have shown that purified GFP-Tus fusion protein or GFP-Tus NLS fusion protein, when added to the culture media, was internalized very efficiently into mammalian cells. Thus, Tus is perhaps the first reported bacterial protein to possess both NLS and NES, and has the capability to transduce protein into mammalian cells.